2004
DOI: 10.1892/0891-6640(2004)18<219:eatopt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Toxicity of Paclitaxel (Taxol) for the Treatment of Canine Malignant Tumors

Abstract: Paclitaxel (Taxol) was administered to 25 dogs with histologically confirmed malignant tumors at a dosage of 165 mg/m2 i.v. over 3-6 hours every 3 weeks. Dogs received premedication with antihistimines and corticosteroids to reduce hypersensitivity reactions. However, 64% of the dogs still experienced allergic reactions. Six dogs (24%) had grade 3 or 4 neutropenia, 6 dogs (24%) required hospitalization and 3 dogs (12%) died of sepsis. Five dogs (20%) had a partial response (osteosarcoma [2 dogs] mammary carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 11 publications
1
37
0
1
Order By: Relevance
“…The toxicity of systemic administration of paclitaxel has been previously determined by Poirier et al in dogs (33). In that study severe myelosuppression was consistently observed in the animals at clinically relevant doses.…”
Section: Discussionmentioning
confidence: 81%
“…The toxicity of systemic administration of paclitaxel has been previously determined by Poirier et al in dogs (33). In that study severe myelosuppression was consistently observed in the animals at clinically relevant doses.…”
Section: Discussionmentioning
confidence: 81%
“…Standard forms of paclitaxel contain ethanol and polyethoxylated castor oil to solubilize it, and dogs are exquisitely sensitive to this formulation. 3,4 Protein-bound paclitaxel, another common form, is a fine particle formulation coated with human serum albumin to increase its water solubility. 5 However, using a foreign protein, such as human albumin in dogs, can also result in a hypersensitivity reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel therapy has been attempted in dogs with spontaneously occurring tumors, and preliminary efficacy was noted with breast and bone cancer. 4 However, toxicity was high; 64% of dogs had hypersensitivity reactions despite heavy pretreatment with diphenhydramine and corticosteroids, and 12% had treatment-related deaths. 4 Yet, preliminary efficacy suggests that this group of drugs would expand our treatment options for dogs if a tolerable formulation existed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One report describes the induction of partial remissions in 2 dogs with macroscopic mammary tumors after treatment with paclitaxel, but the overall toxicity was high. 22 To the authors' knowledge, docetaxel has not been used for the treatment of tumors in dogs. The dose of 30 mg/m used in this study was derived from preclinical studies in Beagle dogs.…”
mentioning
confidence: 99%